Improving Early Childhood Language Development through Storytelling Methods - Suci Wahyuni; Thania Diyelsa Aveta Deni (Universitas Negeri Padang, 2019)
Language is an ability possessed by someone to communicate with others, both verbal communication, writing, facial expressions, sign language, gestures, and others. Language skills in children always develop according to their age level. Therefore it is very necessary stimulation from parents and control of these developments because it will affect and determine how the child’s next language development. It can be done by parents by giving examples of good language to children, talking about positive things and easily understood by children.Keywords: Stimulation, Language Ability, Communication, Telling Stories